DNA sequencing of whole human cytomegalovirus genomes from formalin-fixed, paraffin-embedded tissues from congenital cytomegalovirus disease cases - Kathy K. Li; Nicolás M. Suárez; Salvatore Camiolo; Andrew J. Davison; Richard J. Orton (PLoS ONE, 2025)
Background Congenital cytomegalovirus disease (cCMV) is uncommon but can be severe. Investigations of the role of genome sequence variation in the causative virus (human cytomegalovirus, HCMV) in clinical outcome have to date depended on small sample numbers derived from fresh tissues. Extensive formalin-fixed, paraffin-embedded (FFPE) cCMV biorepositories established worldwide potentially provide much larger sample numbers for future investigations. However, there are no published reports of sequencing whole HCMV genomes from such material. Objective To sequence whole HCMV genomes from cCMV FFPE material Study design Sixteen FFPE samples of foetal kidney or placental tissue were processed from ten cCMV cases in foetuses or neonates. Two commercial kits for extracting DNA from FFPE material were evaluated, HCMV DNA was enriched in the extracts, and the samples were sequenced on the Illumina platform. The sequence read datasets were analysed by genotyping, genome assembly and variant calling using a published software pipeline. Results Whole HCMV genomes were sequenced for five cases using either DNA extraction kit. Conclusions Sequencing whole HCMV genomes from cCMV FFPE material is feasible. This potentially facilitates future studies of the effects of HCMV variation on the clinical outcome of cCMV.